Effects of ocean acidification and nitrogen limitation on the growth and photophysiological performances of marine macroalgae Gracilariopsis lemaneiformis - Yang, Yuling; Li, Wei; Li, Yahe; Xu, Nianjun (Frontiers in Marine Science, 2024)
To investigate the effects of ocean acidification (OA) and nitrogen limitation on macroalgae growth and photophysiological responses, Gracilariopsis lemaneiformis was cultured under two main conditions: ambient (Low CO2, LC, 390 μatm) and CO2 enriched (High CO2, HC, 1000 μatm), with low (LN, 7 μmol L-1) and high (HN, 56 μmol L-1) nitrate. High CO2 levels decreased growth under both LN and HN treatments. HC reduced Chl a, carotenoids, phycoerythrin (PE), and phycocyanin (PC) under HN conditions, while only Chl a decreased under LN conditions. NO3- uptake rate was restricted under LN compared to HN, while HC enhanced it under HN. Net photosynthetic O2 evolution rates did not differ between CO2 and nitrate treatments. Dark respiration rates were higher under HN, further boosted by HC. The stimulated effective quantum yield (Y(II)) corresponded to decreased non-photochemical quenching (NPQ) under HN conditions. Nitrate, not CO2, showed significant effects on the relative electron transport rate (rETRmax), light use efficiency (α) and saturation light intensity (Ik) that with lowered rETRmax and α under LN culture. Our results indicate that OA may negatively affect Gracilariopsis lemaneiformis growth and alter its photophysiological performance under different nutrient conditions.